A structural perspective on tail-anchored protein biogenesis by the GET pathway. (August 2018) - Mateja, Agnieszka; Keenan, Robert J
Abstract : Many tail-anchored (TA) membrane proteins are targeted to and inserted into the endoplasmic reticulum (ER) by the `guided entry of tail-anchored proteins' (GET) pathway. This post-translational pathway uses transmembrane-domain selective cytosolic chaperones for targeting, and a dedicated membrane protein complex for insertion. The past decade has seen rapid progress towards defining the molecular basis of TA protein biogenesis by the GET pathway. Here we review the mechanisms underlying each step of the pathway, emphasizing recent structural work and highlighting key questions that await future studies.